2012
DOI: 10.1111/j.1542-4758.2012.00684.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of steal syndrome in hemodialysis patients

Abstract: Steal syndrome is a feared complication of dialysis vascular access in a population becoming older and frailer. The aim of this study was to determine the predictor factors of steal syndrome. All proximal arteriovenous fistulas (AVFs), patent at day 30, inserted between January 2008 and December 2009 were studied. Data on age, gender, diabetes mellitus (DM) status, presence of coronary or peripheral artery disease, date of initiation of renal replacement therapy, date of access construction, localization, type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 20 publications
(48 reference statements)
1
26
2
4
Order By: Relevance
“…Intuitively one might speculate that a dual outflow tract of both a cephalic and a basilic vein as in Gracz‐AVF leads to a higher risk of hand ischemia. In one retrospective study on brachial artery‐based AVFs, 65% of patients that developed hand ischemia harbored a Gracz‐type fistula compared to 41% of patients without ischemic complaints . Interestingly, in one study on SB ligation, isolated ligation of the basilic vein sufficiently increased intraoperative DBI in only one patient whereas ligation of additional SBs was required in four patients .…”
Section: Discussionmentioning
confidence: 99%
“…Intuitively one might speculate that a dual outflow tract of both a cephalic and a basilic vein as in Gracz‐AVF leads to a higher risk of hand ischemia. In one retrospective study on brachial artery‐based AVFs, 65% of patients that developed hand ischemia harbored a Gracz‐type fistula compared to 41% of patients without ischemic complaints . Interestingly, in one study on SB ligation, isolated ligation of the basilic vein sufficiently increased intraoperative DBI in only one patient whereas ligation of additional SBs was required in four patients .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the risk of sepsis, graft explantation was performed. Only two patients developed steal syndrome in this study (LG‐group), both classified as stage 1, and not requiring intervention.…”
Section: Discussionmentioning
confidence: 84%
“…5, 8, 13-16 Rocha et al 26 reported that female gender, diabetes, and side-to side anastomoses were predictors in their multivariate model with diabetes being the strongest predictor (OR 3.08, CI 1.2 – 8.2). The presence of coronary artery disease has been an inconsistent predictor of ARHI in contrast to our finding.…”
Section: Discussionmentioning
confidence: 98%